2015
DOI: 10.23960/jat.v3i2.2014
|View full text |Cite
|
Sign up to set email alerts
|

Karakterisitk Sifat Fisik Tanah Pada Lahan Produksi Rendah Dan Tinggi Di Pt Great Giant Pineapple

Abstract: Sifat fisik tanah merupakan sifat tanah yang berpengaruh terhadap pertumbuhan dan poduksi tanaman karena akan menentukan penetrasi akar di dalam tanah, kemampuan tanah menahan air, drainase, aerasi tanah dan ketersediaan unsur hara tanah. Penelitian ini bertujuan untuk mempelajari dan mengetahui karakteristik sifat fisik yang terdapat pada lahan yang berproduksi rendah dan tinggi. Penelitian dilaksanakan dari bulan Juni sampai September tahun 2013 diPT Great Giant Pineapple (GGP), Lampung Tengah. Penelitian di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 1 publication
0
11
0
4
Order By: Relevance
“…It has been reported that the main limiting factor in Ultisols is lack of nutrient P, aeration and porosity characteristics, low stability index, and Fe and Al oxidation, so crop productivity can still be optimized with proper soil management practices (Aji et al, 2022;Cristancho et al, 2011;Holilullah et al, 2015;Igwe et al, 2013). On the other hand, in Histosols, the limiting factors that can affect crop productivity include high acidity, low fertility, low density, susceptibility to excessive drought, lack of micronutrients, and nutrient imbalances (Rinaldi et al, 2019;Wigena, Subardja, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the main limiting factor in Ultisols is lack of nutrient P, aeration and porosity characteristics, low stability index, and Fe and Al oxidation, so crop productivity can still be optimized with proper soil management practices (Aji et al, 2022;Cristancho et al, 2011;Holilullah et al, 2015;Igwe et al, 2013). On the other hand, in Histosols, the limiting factors that can affect crop productivity include high acidity, low fertility, low density, susceptibility to excessive drought, lack of micronutrients, and nutrient imbalances (Rinaldi et al, 2019;Wigena, Subardja, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of twisted disease and cultivation practice of shallot farmers 25 disease was not found in Sono during the dry season (Table 2). Holilullah et al (2015) explained that soils with granular/crumb structures have higher porosity than soils with massive/solid structures. Soil with a sand texture has macropores, making it difficult to hold water.…”
Section: Soil Characteristics and Cropping Patternmentioning
confidence: 99%
“…Tanah memiliki sifat yang berbeda-beda sehingga tanah pada dataran tinggi dan rendah tentu menghasilkan hasil produksi yang berbeda. Untuk memperbaiki struktur tanah, pemberian pupuk organik merupakan salah satu cara untuk memperbaiki sifat fisik tanah (Holilullah et al, 2015). Penelitian terhadap jenis-jenis tanah perlu dilakukan untuk menunjang pertumbuhan suatu tanaman.…”
Section: Abstrakunclassified